PERAN BADAN PERMUSYAWARATAN DESA DALAM PEMBANGUNAN DESA : Studi Desa Aeng Batu-batu Kecamatan Galesong Utara Kabupaten Takalar - Hasdi, M. Abid Ibnu; Mustafa, Adriana (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2023)
This study aims to find out the role of the Village Consultative Body in village development in Aeng Batu-Batu Village, North Galesong District, Takalar Regency. This type of research is empirical legal research with a normative juridical approach. The results showed that the Village Consultative Body in Aeng Batu-Batu Village, North Galesong District, Takalar Regency substantially had a role in establishing village regulations, a forum for village community aspirations and village government performance oversight institutions. However, the implementation of the Village Consultative Body in Aeng Batu-Batu Village experienced various obstacles including community participation, level of education, collaboration with the Village Head, and lack of technical guidance on administering village governance by the Takalar district government causing the BPD to experience difficulties in establishing village regulations together with Village head.